Research on the impact of tourism cooperation on urban public health - Zhao, Liang; Zhou, Guolei; Li, Chen (Frontiers in Public Health, 2025)
IntroductionTourism cooperation is increasingly recognized as a key driver of regional economic development, playing a crucial role in facilitating internal circulation and enhancing urban public health. This study examines the relationship between tourism cooperation and urban public health development, with a focus on China.MethodsUsing data from 284 Chinese cities over the period 2011-2022, this research measures both the degree of tourism cooperation and the level of urban public health development. Empirical analysis is conducted to assess the impact of tourism cooperation on urban public health outcomes. The study employs robustness tests to ensure the validity of its findings.ResultsThe findings indicate that tourism cooperation significantly promotes urban public health development. After conducting robustness tests, this result remains consistent. Furthermore, heterogeneity analysis reveals that the “core hinterland” type of tourism cooperation model has a stronger impact on urban public health development compared to the adjacent city type. Among different city cooperation models, tourism cooperation between central cities has the greatest empowering effect, followed by cooperation between central and non-central cities, while cooperation between non-central cities has the smallest effect.DiscussionThe research suggests that tourism cooperation can effectively address regional economic disparities and the imbalanced development of urban public health in China. The findings have important implications for policy-making, particularly in promoting sustainable urban health development and narrowing regional gaps in economic and health outcomes.